Identifying the Critical Barriers Factors to the Implementation of Building Information Modelling (BIM) in the Sarawak's Construction Industry - Toe Myint Naing; Aidin Nobahar Sadeghifam; Meheron Selowara Joo (Tecno Scientifica Publishing, 2022)
Building Information Modelling (BIM) is one of the most advanced developments in the architecture, engineering, and construction (AEC) industry that can generate a 3D virtual information model which can be used for planning, design, construction, and operations. As Building Information Modelling (BIM) approaches the construction industry as a new technology and process, changes in the industry have created some barriers to BIM adoption in Malaysia. This research aims to enhance the implementation of BIM in the construction stage of Sarawak's construction industry by identifying and classifying the critical barriers. This study fills this current knowledge gap and enhances the understanding of BIM in the construction stage and the factors that hinder implementation in Sarawak. To develop the challenges being faced in this industry, a set of barrier clusters based on people, process, policy, technology, and cost were pre-identified through a literature review, and a structured interview involving three BIM experts was conducted on WebEx to refine these barriers with the current industry situation. As an outcome, this study identified 49 of the barriers from the literature and refined them into 26 of the barriers under their main clusters. Interestingly, they all validated the fact that lack of government involvement in BIM implementation is an undeniable barrier factor to growing BIM utilization and reaching its full potential. This study will form the basis of further research, and additional studies focusing on prioritizing these identified barriers for strategic planning would help the construction players in their swift transformation to BIM.